Eucalyptus Psyllid, Blastopsylla occidentalis Taylor and Red Gum Lerp Psyllid, Glycaspis brimblecombei Moore (Insecta: Hemiptera: Psyllidae) - Susan E. Halbert; Raymond Gill; James N. Nisson (EDIS)
Two psyllids that feed on Eucalyptus were found for the first time in Florida in the spring of 2001 in tourist parks in the Orlando area: Glycaspis brimblecombei Moore, the red gum lerp psyllid, and Blastopsylla occidentalis Taylor, the eucalyptus psyllid. Both species originate in Australia and already are well established in California, which is the most likely immediate source of the Florida populations. This document is EENY-306 (originally published as DPI Entomology Circular 407), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: October 2003.